Splenic siderosis and parenteral iron dextran in maintenance haemodialysis patients. Issue 1 (January 1984) - Murray, J A; Slater, D N; Parsons, M A; Fox, M; Smith, S; Platts, M M
Abstract : The histological features of 40 spleens surgically removed from maintenance haemodialysis patients are reported. Twenty-four of the 40 (60%) showed massive iron loading and a significant direct correlation was found between iron loading and the amount of intravenous iron dextran administered. Since parenteral iron dextran appears to be a major factor in causing iron overload in haemodialysis patients its use as a method of iron replacement in these patients would appear inappropriate.